Feed and seed productivity of alfalfa in the conditions of the Southern Forest Step of Ukraine - Antonets, O.; Kocherga, V. (Scientific Progress & Innovations, 2025)
Alfalfa is one of the oldest perennial leguminous crops used for animal feed. It is well eaten in its pure form and in a mixture with perennial cereal grasses. This grass is a source of high-protein feed, rich in vitamins, carbohydrates, macro- and microelements. In terms of feed value, this plant is an unsurpassed crop. It contains over 200 g of digestible protein in 1 feed unit of leaf and stem mass. Alfalfa has a high yield of green mass, namely 50–60 t/ha and hay 10–12 t/ha. The unique biological features of alfalfa are its perennial and multi-mowing use as a herbage. Alfalfa also improves soil fertility and structure. Therefore, the relevance of the study was to analyze collection samples of alfalfa and bastard lucerne for feed and seed productivity in the conditions of the Southern Forest-Steppe of Ukraine. The aim of the study is to determine the biological potential of alfalfa collection samples. The experiment studied 19 collection samples of bastard lucerne (Medicago varia Martyn) and 3 collection samples of alfalfa (Medicago sativa L.) – UJ070001, UJ700003 and UJ700456. The studies were conducted on crops of the second and third years in 2022 and 2023 at the Ustymivka Experimental Station of Plant growing of the Institute of Plant growing named after V. Ya. Yuriev of NAAS of Ukraine (Ustymivka ESP).The station is located in the southern part of the Forest-Steppe of Ukraine. The largest total weight of green mass for two slopes in 2023 was given by collection samples of alfalfa UJ070001 (5280 g/m2), UJ700003 (5350 g/m2) and bastard lucerne UJ700053 (5430 g/m2), UJ700518 (5240 g/m2), UJ700486 (5230 g/m2). The highest hay yield for two slopes in 2023 was also shown by the collection samples of alfalfa UJ070001 (1520 g/m2), UJ700003 (1340 g/m2) and the bastard lucerne UJ700053 (1550 g/m2), UJ700518 (2480 g/m2), UJ700486 (1460 g/m2). The seed yield per plot of all collection samples of alfalfa was higher in 2023. So, the best over the years of research on feed and seed productivity were the collection samples of alfalfa (Medicago sativa L.) UJ070001 and UJ700003 and the collection samples of bastard lucerne (Medicago varia Martyn) UJ700053, UJ700518, UJ700486.